Peran Guru Menciptakan Disiplin Kelas Terhadap Peningkatan Prestasi Belajar Siswa di Madrasah Ibtidaiyah Muhammadiyah 11 TPAY Blimbing Paciran Lamongan - Mahfud, Zainal; Santoso, Subhan Adi (STIT Muhammadiyah Paciran, 2021)
The focus of the research discussed in this thesis is (1) How is the role of the teacher in creating classroom discipline at MI Muhammadiyah 11 TPAY Blimbing Paciran Lamongan, (2) How is student learning achievement at MI Muhammadiyah 11 TPAY Blimbing Paciran Lamongan, (3) Is there a correlation between the role of teachers in creating classroom discipline with student achievement at MI Muhammadiyah 11 TPAY Blimbing Paciran Lamongan. This study uses methods including: population, sample, data sources, data collection methods and data analysis techniques. In this study it can be concluded that there are four roles that must be carried out by a teacher in creating classroom discipline, namely the teacher as the first implementer of the rules, the teacher as a student director in carrying out all school rules, the teacher as a student supervisor in carrying out all school rules and the teacher providing rewards and punishments for students. Student achievement of MI Muhammadiyah 11 TPAY Blimbing Paciran Lamongan in the 2014/2015 academic year showed a sufficient value. There is a correlation between the teacher's role in creating classroom discipline to improving student achievement at MI Muhammadiyah 11 TPAY Blimbing Paciran Lamongan and the correlation shown is quite a correlation with a score of 0.698.